Enhancing academic resilience through motivation and strategy: evidence from Malaysian boarding schools using SDT - Mohd Sofian Omar Fauzee; Shaohua Zhang; Marni Ishak; Li Ma; Mo Hou; Wenjie Zhang; Muhammad Nazrul Hakim Abdullah; Akhmad Habibi; Daljit Singh Gurbaksh Singh; Mohd Hanafi Mohd Yasin; Wan Suraya Wan Nik (Institute of Advanced Engineering and Science, 2026)
This study investigates the relationship between student motivation and self-regulated learning strategies among Malaysian boarding school students, using self-determination theory (SDT) as its theoretical foundation. A total of 328 form four students from four northern Malaysian boarding schools participated. Using a validated version of the motivated strategies for learning questionnaire (MSLQ) and analyzed through second-order partial least squares structural equation modeling (PLS-SEM), results revealed a significant positive relationship between motivational beliefs, especially self-efficacy and intrinsic value, and self-regulated learning strategies. The study’s novelty lies in validating a culturally adapted, second-order motivation model tailored to Malaysian boarding schools. Notably, the research isolates the mediating effect of intrinsic motivation on self-regulation within a high-pressure, collectivist setting, extending SDT’s applicability. However, limitations lie in the use of a cross-sectional design and dependence on self-reported data, and regional focus. Future studies should adopt longitudinal designs, consider diverse school types, and integrate perspectives from teachers or parents to strengthen validity. Including objective academic performance metrics may offer deeper insight. This research affirms the relevance of SDT in Malaysia’s education system and provides a validated framework linking motivation to strategic learning. The findings support evidence-based pedagogical strategies and align with sustainable development goal (SDG) 4 on quality education and goal 10 on reduced inequalities, promoting for fair and motivation-enhancing environments of learning.